Effects of multidimensional exercise management on self-efficacy, blood glucose control, and delivery outcomes in pregnant women with gestational diabetes mellitus - He, Ying; Liu, Xin; Yang, Xiali (Frontiers in Physiology, 2024)
Objective This study aimed to evaluate the effects of multidimensional quantitative exercise management on self-efficacy, blood glucose control, and delivery outcomes in pregnant women with gestational diabetes mellitus (GDM). Methods A randomized controlled trial was conducted with 150 pregnant women diagnosed with gestational diabetes mellitus (GDM). Participants were randomly assigned to either the experimental group (Exp), which received a multidimensional quantitative exercise management intervention, or the control group (Con), which received standard GDM management. Results were compared between the groups included self-efficacy scores, blood glucose levels, and delivery outcomes. Results Exp group of pregnant women exhibited drastically superior self-efficacy scores as well as more stable blood glucose levels during pregnancy relative to Con group (P < 0.05). Moreover, visual analogue scale (VAS) of pregnant women and Apgar scores of infants in Exp group were considerably better than those in Con group (P < 0.05). In contrast to Con group, pregnant women in Exp group had considerably better labor outcomes along neonatal complication rates (P < 0.05). Conclusion Multidimensional quantitative exercise management had a positive impact on pregnant women with GDM. This intervention method can improve self-efficacy levels along better blood glucose control, and enhance delivery outcomes. These findings suggested that multidimensional quantitative exercise management has potential clinical value in the management of GDM, providing an effective management strategy to improve the health conditions of both pregnant women and infants.